Physical properties and biological fate of OSA-modified-starch-stabilized emulsions containing β-carotene: Effect of calcium and pH. (April 2018) - Lin, Quanquan; Liang, Rong; Zhong, Fang; Ye, Aiqian; Singh, Harjinder
Abstract: Understanding the roles of the calcium ion in both the physical properties of emulsions and the biological fate of the emulsion during digestion is important for the rational design of emulsion-based delivery systems that can moderate lipid digestion and the bioaccessibility of bioactive compounds. The effect of CaCl2 on the zeta-potential, the particle size, and the microstructure of emulsions, the rate and extent of lipid digestion, and the bioaccessibility of β-carotene in emulsions stabilized by octenyl succinic anhydride (OSA)-modified starches was investigated in an in vitro mouth/stomach/intestine model system. The addition of CaCl2 to starch solutions at pH 7.0 before homogenization decreased the emulsifying ability of the OSA-modified starches. When the concentration of added CaCl2 increased, the particle size of the emulsions increased and the creaming stability decreased. At pH 3.0, CaCl2 had no influence on the physical properties of OSA-modified-starch-stabilized emulsions. However, the influence of calcium on the biological fate of emulsions containing β-carotene was independent of the emulsion pH. The addition of CaCl2 promoted the digestion of lipid but decreased the bioaccessibility of β-carotene in both emulsions made at pH 7.0 and emulsions made at pH 3.0. The effect of CaCl2 on the biological fate of the emulsions was attributed mainly to the interaction of the calcium ion with lipolytic products and bile salts, which seemed to offset the effect of structure and physical properties. Graphical abstract: Image Highlights: CaCl2 decreased the emulsifying ability of OSA-modified starch at pH 7.0. No effect of CaCl2 on physical properties of emulsions at pH 3.0. Calcium promoted the digestion of lipid in emulsions made at pH 7.0 and pH 3.0. Calcium reduced the β-carotene bioaccessibility in emulsions made at pH 7.0 and 3.0.